Réponses

2014-10-31T15:58:47+01:00
1)  f(x)=0      :4-(x-1)²=0⇒ (2-(x-1) (2+(x-1)=0                                                                                         ⇒ (2-x+1) (2+x-1)=0                                                                                         ⇒ (3-x) (1+x)=0                                                                                               ⇒ (3-x)=0 ∨ (1+x)=0                                                                                         ⇒ 3-x=0 ∨ 1+x=0                                                                                            ⇒ x=3  ∨   x=-1                                                                2)  f(x)=4                                                                                                                          3-x=4  ∨  1-x=4  ⇔ x=7  ∨ x=3